(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides information on the issues of regulation and effective organization of classroom leadership activities in secondary schools. In addition, recommendations were made regarding the methods of working with students with low mastery in the class team and developing their basic competencies, as well as using interactive methods to increase students’ creativity, to develop them as creative and well-rounded individuals who think critically.